The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/micr.30837
|View full text |Cite
|
Sign up to set email alerts
|

Outcome comparison between thoracodorsal artery perforator flap and muscle‐sparing latissimus dorsi flap in axillary reconstruction after hidradenitis suppurativa excision

Abstract: Background Thoracodorsal artery perforator (TDAP) flap and muscle‐sparing latissimus dorsi (MSLD) flap have been frequently used for axillary coverage after hidradenitis suppurativa (HS) excision. However, none showed superiority to others. This study compared both flaps to define the ideal option, highlighting flap outcomes and functional and aesthetic results. Methods A retrospective study was conducted to compare both flaps that were used for axillary reconstruction in nine patients with bilateral HS Hurley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The TDAP flap vascularization is based on the perforators originating from either the transverse or the descending branch of the thoracodorsal artery, which, like the circumflex scapular artery, originates from the subscapular artery (La Padula et al, 2023). These vessels are normally located 8 cm below the axillary fold, thus making this flap particularly suited for breast and axillary reconstructions, in particular for the treatment of HS (El‐Shebly et al, 2022; Horta et al, 2023). However, the main drawback of this procedure is related to the anatomy of its perforator vessels, which is much more variable compared to the CSAP flap.…”
Section: Discussionmentioning
confidence: 99%
“…The TDAP flap vascularization is based on the perforators originating from either the transverse or the descending branch of the thoracodorsal artery, which, like the circumflex scapular artery, originates from the subscapular artery (La Padula et al, 2023). These vessels are normally located 8 cm below the axillary fold, thus making this flap particularly suited for breast and axillary reconstructions, in particular for the treatment of HS (El‐Shebly et al, 2022; Horta et al, 2023). However, the main drawback of this procedure is related to the anatomy of its perforator vessels, which is much more variable compared to the CSAP flap.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other systems, damage to the arterial system of the latissimus dorsi has a spectrum of presentations. For example, those at a proximal level present with severe bleeding and require emergency surgical intervention to control the resulting hemorrhage and revascularize the muscle [ 16 , 17 , 18 ]. With all flap transfers, if the vascular pedicle is not functional, there will be a greater risk of muscle necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…When specifically comparing the flaps derived from the latissimus dorsi, both TDAP and muscle-sparing latissimus dorsi (MSLD) have advantages. While MSLD has a shorter procurement time, TDAP is less bulky [ 16 ], which may offer greater comfort for the patient in terms of functionality. Furthermore, as exhibited by Elgohary et al surgical management of stage III HS of axilla by TDAP flap showed good aesthetic and functional results with a 100 % success rate in eradicating and complete remission of the disease during the follow-up period [ 17 ].…”
Section: Discussionmentioning
confidence: 99%